Pyrotinib Plus Vinorelbine Versus Lapatinib Plus Capecitabine in Patients With Previously Treated HER2-Positive Metastatic Breast Cancer: A Multicenter, Retrospective Study - Xie, Yizhao; Li, Yi; Ting, Luo; Sang, Die; Yuan, Peng; Li, Wei; Li, Huihui; Ge, Rui; Wang, Biyun (Frontiers in Oncology, 2021)
Background Pyrotinib is a newly-developed irreversible pan-ErbB (erythroblastic leukemia viral oncogene homolog) receptor oral tyrosine kinase inhibitor (TKI) with promising efficacy in the human epidermal growth factor receptor-2 (HER2) positive breast cancer. The phase III PHOEBE study proved that pyrotinib plus capecitabine exceeded lapatinib plus capecitabine (LX) in PFS (p < 0.001). Oral vinorelbine is commonly used in combination with anti-HER2 treatment. However, no evidence was reported in terms of the real-world pattern, safety, and efficacy of pyrotinib plus vinorelbine (NP) compared with LX. Methods Medical records were retrospectively evaluated for all HER2-positive metastatic breast cancer (MBC) patients who experienced progression on prior trastuzumab-containing regimens (advanced setting) and taxane (any setting) and received NP or LX therapy from 2015 to 2021 in five institutions. Results A total of 224 patients were enrolled and evaluated, of which 132 (58.9%) patients received LX and 92 (41.1%) patients received NP. The median progression-free survival (mPFS) of NP group was significantly longer than that in LX group (8.3 vs 5.0 months, HR = 0.47 95% CI 0.34–0.65, p < 0.001). The advantage of NP over LX was seen both in patients with trastuzumab resistance (p < 0.001) and refractoriness (p = 0.004). The NP group had more diarrhea cases (23.9%) compared to the LX group (8.3%). Discontinuation rates in the two groups were similar. Conclusions This trial revealed the clinical practice of NP and LX treatment among HER2+ MBC patients pretreated with trastuzumab in China. More patients received LX than NP in real-world while the efficacy of NP exceeded LX in terms of PFS regardless of resistant status of trastuzumab. Although the NP group had more diarrhea cases, toxicities in both groups were acceptable.